2020
DOI: 10.1111/1754-9485.13092
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement in paediatric radiation oncology through peer review

Abstract: Introduction: Around 300 children in Australia and New Zealand (ANZ) undergo a course of radiation treatment (RT) each year. A fortnightly videoconference for radiation oncologists managing children started in 2013. We conducted an audit of the videoconference to assess its influence on the care of children who receive RT in ANZ. Methods: De-identified data from minutes (August 2013-December 2019) were analysed retrospectively using three categories: meeting participation, case presentations and management dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Symptomatic brain stem injury (SBI), including pathologically verified radiation necrosis or newly appeared areas of contrast enhancement on MRI following PBT, has been reported to be either 3.8% at 2 years [ 73 ] or 2% at 5 years [ 74 ] or 3.2% as crude incidence [ 75 ]. These values are similar to those reported with standard XRT [ 76 ]. Younger age, higher radiation doses, and pre-treatment with high-dose chemotherapy are considered risk factors for SBI after PBT.…”
Section: Brain Injury Following Particle Therapysupporting
confidence: 90%
“…Symptomatic brain stem injury (SBI), including pathologically verified radiation necrosis or newly appeared areas of contrast enhancement on MRI following PBT, has been reported to be either 3.8% at 2 years [ 73 ] or 2% at 5 years [ 74 ] or 3.2% as crude incidence [ 75 ]. These values are similar to those reported with standard XRT [ 76 ]. Younger age, higher radiation doses, and pre-treatment with high-dose chemotherapy are considered risk factors for SBI after PBT.…”
Section: Brain Injury Following Particle Therapysupporting
confidence: 90%
“…Further studies suggested that the change rate was closer to 10% with the major change rate to be approximately 2% of reviewed cases. [21][22][23] Our study only collected data on whether there was a change recommended or not and did not distinguish between minor or major change, as per the recommended PRAT data points at the time of this study. Definitions of minor and major change have since been outlined in the revised PRAT document and applied to our prospective TPRM data collection.…”
Section: Discussionmentioning
confidence: 99%
“…A group of paediatric ROs reported their experience of a videoconference peer review meeting between 2013 and 2019, with regular attendance from 4 of 11 centres treating children with radiation therapy across Australia and New Zealand 35 . One in six of the expected children undergoing radiotherapy across the two countries underwent peer review, with changes recommended in 13% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia and internationally, peer review has been reported to improve patient care both directly and indirectly and be feasible within radiation oncology facilities 6–35 . The American Society for Radiation Oncology (ASTRO) surveyed members in 2013 to establish peer review practice patterns, 36 with the majority of the 572 participating physicians supporting formal recommendation and guidance on peer review.…”
Section: Introductionmentioning
confidence: 99%